Healthy Living for Elders: Tips For Taking Over-The-Counter Medicine - Jennifer Hillan (EDIS)
Nonprescription, over-the-counter (OTC) medications are often a convenient and inexpensive way to treat minor health problems. However, OTC products are serious medicines that can cause unwanted problems if used incorrectly. If you are taking OTC products, this document lists some guidelines to help you use them safely. This is document FCS 8624-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultrual Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.